Prognostic role of tumor-infiltrating lymphocytes in gastric cancer: a meta-analysis and experimental validation - Zhang, Nana (Arch Med Sci, 2019)
INTRODUCTION: We performed a meta-analysis and an experimental validation to investigate the association between tumor infiltrating lymphocytes (TILs) and the outcome of gastric cancer (GC) patients to provide prognostic indicators for clinical practice. MATERIAL AND METHODS: The relative literature of TILs in tumor tissue from patients with gastric cancer was searched from PubMed, Embase, NIH databases, from April 2000 to 31 December 2016. Studies on the prognostic value of TILs as CD3+, CD4+, CD8+, GrB+, and FOXP3+ lymphocytes for GC were retrieved, and also the related references were traced as supplements. Independent screening documents, extracting information and evaluating quality were implemented independently by 2 evaluators according to the inclusion and exclusion criteria, which were then analyzed by meta-analysis using STATA version 12.0 software. RESULTS: The results indicated that high levels of intratumoral CD8+, CD3+ and CD4+ T cell infiltration were associated with better overall survival(OS) in gastric cancer patients, while high density of intratumoral FOXP3+ T cells was not closely associated with a worse outcome. Additionally, in our study, higher density of granzyme B+ (GrB+) T cell infiltration indicated an optimistic prognosis, and infiltration of a larger number of general TILs also suggested a favorable prognosis by log-rank test analysis. CONCLUSIONS: This meta-analysis clarified that high levels of CD8+, CD3+, and CD4+ T cell infiltration in tumor tissue showed better OS in GC patients, whereas high density of FOXP3+ T cell infiltration may not be recognized as a negative prognostic factor. These results may provide some useful prognostic indicators for clinical application in gastric cancer.